Impact of public environmental concern on green technology innovation: a case study of the Yangtze River Delta in China - Shengmei Hu; Shengmei Hu; Hongbing Deng; Hongbing Deng; Hongrui Jiao; Hongrui Jiao; Shuang Qin; Shuang Qin (Frontiers in Environmental Science)
This study explores the impacts of PEC on green technology innovation (GTI), which includes both independent green technology innovation (IGTI) and cooperative green technology innovation (CGTI). It also analyzes the threshold effects of green finance (GF) and information and communication technology (ICT) to unlock the growth potential of GTI. To achieve this, we employ a two-way fixed-effects model and a threshold-effects model, utilizing city panel data from the Yangtze River Delta region of China, covering the years 2011–2020. The results indicate that PEC has a positive effect on GTI, IGTI, and CGTI. However, its impact on CGTI is relatively weaker. These findings remain valid after several robustness tests. Heterogeneity analysis shows that PEC promotes IGTI in research organizations, yet it fails to do so in firms. PEC enhances CGTI within cities, but not between them. Additionally, PEC positively affects GTI only when GF and ICT surpass certain thresholds. The threshold effect of GF is limited to IGTI, whereas ICT’s threshold effect is more stringent in CGTI. Based on these conclusions, we provide insights on leveraging public concerns to promote the growth of green innovation and how governments can create a favorable external environment for this.